K-Means Cluster Analysis of Sex, Age, and Comorbidities in the Mortalities of Covid-19 Patients of Indonesian Navy Personnel - suharjo, bambang; Utama, Muhammad Satria Utama (JISA(Jurnal Informatika dan Sains), 2021)
Covid-19 disease is still ongoing. It is necessary to do intensive research related to age, sex and congenital diseases so that management can be better planned. The research was conducted using data from Indonesian Navy personnel and their families, retired Indonesian Navy and their families. This study used k-means clustering for data grouping of Indonesian Navy personnel based on age, sex and congenital disease characteristics. The results of the k-means cluster clustering show that the k = 2 cluster has not been able to provide an explanation of the relationship between age, sex and comorbidity with the risk of death due to Covid-19. However, in the cluster with k = 3, it turns out that deaths due to Covid-19 are related to old age, men, even though there is no congenital disease. Meanwhile, using the k = 4 cluster, it is increasingly clear that deaths due to Covid-19 are closely related to old age, both men and women, with comorbidities.